Acetate suppresses myocardial contraction via the short-chain fatty acid receptor GPR43 - Jiang, Xuan; Zhang, Ying; Zhang, Huaxing; Zhang, Xiaoguang; Yin, Xiaopeng; Yuan, Fang; Wang, Sheng; Tian, Yanming (Frontiers in Physiology, 2022)
The heart has high energy requirements, with an estimated 40-60% of myocardial ATP production derived from the oxidation of fatty acids under physiological conditions. However, the effect of short-chain fatty acids on myocardial contraction remains controversial, warranting further research. The present study sought to investigate the effect and mechanism of acetate on myocardial contraction in rat ventricular myocytes. Echocardiography and Langendorff heart perfusion were used to evaluate cardiac function. Cell shortening and calcium transient were measured in isolated cardiomyocytes. The patch-clamp method determined the action potential and L-type Ca2+ current in cardiomyocytes. Moreover, the expression of GPR43 in cardiomyocytes was examined by immunofluorescent staining and Western blot. We demonstrated that acetate transiently reduced left ventricular developmental pressure in isolated Langendorff heart perfusion model, with no effect on stroke volume and cardiac output in vivo. In addition, acetate transiently and reversibly inhibited cardiomyocyte contraction and calcium transient. Acetate did not affect the action potential and L-type Ca2+ current in cardiomyocytes. As a short-chain fatty acid receptor, GPR43 was expressed in rat cardiomyocytes. Furthermore, the GPR43 antagonist GLPG0974 prevented the acetate-induced inhibitory effect on myocardial contraction. We conclude that acetate transiently inhibits contraction via the short-chain fatty acid receptor GPR43 in cardiomyocytes.